Reworking research: Interactions in academic articles and blogs. (December 2019) - Zou, Hang; Hyland, Ken
The blog is an increasingly familiar newcomer to the panoply of academic genres, offering researchers the opportunity to disseminate their work to new and wider audiences of experts and interested lay people. This digital medium, however, also brings challenges to writers in the form of a relatively unpredictable readership and the potential for immediate, public and potentially hostile criticism. To understand how academics in the social sciences respond to this novel rhetorical situation, we explore how they discoursally recontextualize in blogs the scientific information they have recently published in journal articles. Based on two corpora of 30 blog posts and 30 journal articles with the same authors and topics, we examine the ways researchers carefully reconstruct a different writer persona and relationship with their readers using stance and engagement model. In addition to supporting the view that the academic blog is a hybrid genre situated between academic and journalistic writing, we show how writers' rhetorical choices help define different rhetorical contexts.